The WTO Agreement and Telecommunications Policy Reform - Cowhey, Peter; Klimenko, Mikhail M. (World Bank, Washington, DC, 2014)
Every country serious about introducing competition finds that the transition from monopoly to competition is both economically rewarding and laden with policy dilemmas. As a new century begins, we have an essentially new market for telecommunications. Digital technology forced a re-examination of the opportunity costs of protecting traditional telecommunications equipment and service suppliers. An inefficient market for telecommunications threatened competitiveness in the computer, software, and information industry markets. Meanwhile, after dislocations created by global stagflation through the early 1980s, developing countries became interested in privatization of state enterprises as a tool of economic reform--and state telephone companies were especially promising targets for privatization. Those countries began exploring options for allowing selective competition, as phone companies in major industrial countries began looking to foreign markets for new business opportunities. The World Trade Organization (WTO) Agreement on Basic Telecommunications Services created a new regime for the world market. Now we must pay close attention to regulatory fundamentals: 1) Low barriers to entry in the market for communications services. 2) Effective re-balancing of rates for services during the market transition. 3) Effective Strong interconnection policies. 4) The creation of independent regulatory authorities with the resources and power necessary to foster competition and safeguard consumer welfare. The authors assess how developing and transition economies have fared in profiting from changes in the telecommunications market. They also examine the policy challenges that remain, paying special attention to the global market and regulatory milieu fostered by the 1997 WTO Agreement. They ask what this latest transformation has taught us about wise management of this vital part of the world economy's infrastructure. They focus on the economics of managing the transition to competition, the design of proper regulatory policies and processes, and the embedding of domestic telecommunications in the world market.